Respuesta :

Answer:

[tex]y=-x^2+12x-27[/tex]

Step-by-step explanation:

The general equation of the parabola is [tex]y=ax^2+bx+c[/tex]

As the parabola passes through [tex](3,0),(9,0)[/tex]

[tex]0=9a+3b+c\,\,\,...(i)\\0=81a+9b+c\,\,\,...(ii)[/tex]

Subtract (i) from (ii)

[tex](81a+9b+c)-(9a+3b+c)=0\\72a+6b=0\\12a+b=0\\b=-12a[/tex]

Also, the parabola passes through [tex](10,-7)[/tex],

[tex]-7=100a+10b+c\,\,\,...(iii)[/tex]

Subtract (i) from (iii)

[tex](100a+10b+c)-(9a+3b+c)=-7-0\\91a+7b=-7[/tex]

Put [tex]b=-12a[/tex]

[tex]91a+7(-12a)=-7\\91a-84a=-7\\7a=-7\\a=-1[/tex]

Put [tex]a=-1[/tex] in [tex]b=-12a[/tex]

[tex]b=-12(-1)=12[/tex]

Put [tex]a=-1,b=12[/tex] in (i)

[tex]0=9a+3b+c\\0=-9+36+c\\0=27+c\\c=-27[/tex]

So, equation is [tex]y=-x^2+12x-27[/tex]

The equation of the parabola is y = -x² + 12x - 27

Parabola is the locus of a point such that the same distance from a fixed line, called the directrix, and a fixed point (the focus) is the same.

The equation of a parabola is in quadratic form. Hence it is given as:

y = ax² + bx + c

At point (3, 0):

0 = a(3²) + b(3) + c

9a + 3b + c = 0      (1)

At point (9, 0):

0 = a(9²) + b(9) + c

81a + 9b + c = 0      (2)

At point (10, -7):

-7 = a(10²) + b(10) + c

100a + 10b + c = -7      (3)

Solving equations 1, 2, 3 gives: a = -1, b = 12, c = -27

The equation of the parabola is hence y = -x² + 12x - 27

Find out more at: https://brainly.com/question/21685473

ACCESS MORE